Fiscal rules management in the EU: differences between fiscally sustainable and unsustainable countries - Brixová, Barbara; Šuliková, Veronika; Siničáková, Marianna; Wyrwa, Joanna (Zielona Góra: Faculty of Economics and Management Press)
The paper examines fiscal sustainability within the European Union (EU), focusing on its key indicator - the long-term cointegration relationship between government revenues and expenditures. Given the EU`s shared monetary framework, understanding fiscal sustainability at both the union level and within individual member states is critical for macroeconomic stability management.
Keywords: fiscal rules; EU-27; cointegration; panel data; primary budget balance; fiscal sustainability